2021 43rd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2021
DOI: 10.1109/embc46164.2021.9630250
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Propagation of Interictal Spikes, Ripples, and Fast Ripples in Intracranial EEG of Children with Refractory Epilepsy

Abstract: Studies on intracranial electroencephalography (icEEG) recordings of patients with drug resistant epilepsy (DRE) show that epilepsy biomarkers propagate in time across brain areas. Here, we propose a novel method that estimates critical features of these propagations for different epilepsy biomarkers (spikes, ripples, and fast ripples), and assess their common onset as a reliable biomarker of the epileptogenic zone (EZ). For each biomarker, an automatic algorithm ranked the icEEG electrodes according to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Moreover, our findings do not provide information regarding the directionality of information flow between epileptogenic and non-epileptogenic regions. Directed connectivity measures may help to map propagation phenomena of ictal and interictal activity 53 , 54 . We also used only one simple measure of graph-theory (i.e., nodal strength) extensively studied in epilepsy 8 , 13 , 55 that might not fully interpret the complexity of abnormal brain networks 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our findings do not provide information regarding the directionality of information flow between epileptogenic and non-epileptogenic regions. Directed connectivity measures may help to map propagation phenomena of ictal and interictal activity 53 , 54 . We also used only one simple measure of graph-theory (i.e., nodal strength) extensively studied in epilepsy 8 , 13 , 55 that might not fully interpret the complexity of abnormal brain networks 56 .…”
Section: Discussionmentioning
confidence: 99%
“…FR Propagate in the SOZ and possibly outside the SOZ Prior studies using SEEG recordings have demonstrated that both ripples (Tamilia et al, 2021(Tamilia et al, , 2018 and fast ripples (Jahromi et al, 2021;Otárula et al, 2019) propagate within the SOZ. These studies did not distinguish HFOs superimposed on spikes from HFOs superimposed on oscillations and thus it is not clear if the propagation of the HFOs on spikes, in these studies, can be attributed to propagation of either the spike, the HFO, or both.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to focus on FR rather than ripples to reduce contamination from normal HFO (Frauscher et al, 2018), but we are aware the generation and propagation of FR could spatially restricted compared to ripples (Bragin et al, 2002;Otárula et al, 2019). Also, we and others use the term "propagate" to explain the time lags observed between FR (Jahromi et al, 2021;Otárula et al, 2019), but recognize delays between FR might be due to a common synaptic driver. Thus, support for our hypothesis would require first, evidence that FR propagate, and we performed several analyses to demonstrate what can best be interpreted as propagation.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Their value in addressing issues such as seizure onset zone (SOZ) localization has been validated [32][33][34][35][36] . Furthermore, the approximate synchrony of recurrent interictal electrographic events across different nodes provides rich spatiotemporal information about the epileptic network 22,[37][38][39] . The earlier discharges within these collective activities have a higher probability to be in the epileptic origin 23,40,41 .…”
Section: Introductionmentioning
confidence: 99%